Central transfers and incentives to collect local revenue among the Central Region of Ghana’s local government officials: analysing the flypaper effect - Christopher Dick-Sagoe; Ernest Ngeh Tingum; Peter Asare-Nuamah; Denis N. Yuni; Nicholas Baidoo (Humanities & Social Sciences Communications)
Abstract Local governments that rely heavily on central transfers are likely to face a laxity problem when increasing locally generated revenues. The flypaper effect identifies this overdependence by examining the relationship between local expenditures and revenues (central transfers and locally generated). Local governments in Ghana depend on central transfers and locally generated revenues to finance local development. Central transfers are important because they balance fiscal capacities across local governments and promote equalisation in the provision of public goods. The study used panel data estimation to analyse revenue, expenditure, distance, and population from 2009 to 2020 for 17 Ghanaian local governments in the Central Region. The results show the presence of the flypaper effect, a situation explained by the fiscal interest model to reduce the effectiveness and efficiency of local government officials as they tend to be less responsive to the needs of the local people they serve. Furthermore, the presence of flypaper effects reduces local governments’ incentives to increase the mobilisation of local revenue. This paper recommends policies that strengthen local government financial autonomy and, consequently, economic development.